LAW FACULTY STUDENTS’ ENGLISH PROFICIENCY AT THE UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA: A Needs Analysis - Fernandes Arung; R. Roslina (Journal of English Education, 2018)
This research was based on the process of inquiry with which the researchers find the problem that needed to be formulated. The problem was the lack of adequate English teaching materials and methods for English learners in the Faculty of Law so that the learning objectives were not achieved maximally. This also led to a lack of interest and motivation to learn. The long-term goal of this research is to provide a significant solution in providing the right teaching materials and methods for English learners as a Foreign Language in the Faculty of Law in the form of syllabus design. In particular, this research aims to provide relevant teaching materials in order to improve the ability to speak English for Law Faculty students so that they can convey their scientific messages in communicating with the proper use of English. This research uses a Qualitative approach with Qualitative Verification method. The participants were six (6) persons selected purposively and consisted of two students of the Faculty of Law, a Law Faculty Lecturer, an employee or a high-ranking prosecutor, and two employees of Jail Kolaka. Data collection techniques used are in-depth interviews, observations, questionnaires, and documentation so that this research instrument is an interview guide, observation sheet, closed questionnaires, and documents. All data were analyzed by using a Coding technique where data were analyzed systematically and objectively to identify characteristics of messages that are more specific so that can bring up a picture of theme sought by researchers. The results of data analysis show that there are some legal topics that can be used as an ideal teaching material for English learner of Faculty of Law such as Legal Issues, Good Governance, International Law, Remission, Case Law, Brach, Law Changing, Constitutional Law, and Career in Law. The proposed learning model is LiWReS (Listen to it, Write what you listen, Read it out loud, and Speak it out in repetition). There are seven (7) tips that can be considered by the faculty to improve motivation, determine the right motives, and increase the interest of English learners Faculty of Law, Universitas Sembilanbelas November Kolaka.